Profit Management and Financial Performance : Analysis of the Influence on Company Value (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of earnings management and financial performance in firm value. The companies used in this study are food and beverage subsector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The method in this study uses a quantitative approach with secondary data in the form of company financial reports. The population in this study were 51 companies, using purposive sampling method and obtained a sample of 11 companies. The data analysis technique uses the classical assumption test, panel data multiple linier regression test, f test and t test, and the coefficient of determination test. The results of this study indicate that earnings management has a significant negative effect on firm value, profitability has a significant positive effect on firm value, earnings management and profitability affect firm value.